Comparison of chemical reaction kinetic models for corn cob pyrolysis - Kiattikhoon Phuakpunk; Benjapon Chalermsinsuwan; Suttichai Assabumrungrat (Energy Reports, 2020)
This study used thermogravimetric analysis to investigate activation energy and pre-exponential factor of corn cob pyrolysis via various model-free methods. For applying kinetics of pyrolysis reaction in commercial simulation tools, a representative single reaction of overall pyrolysis reaction would be preferable in provided toolboxes. However, the kinetic parameters for this single reaction should be suitable to cover all the conversion range. Thus, the kinetic parameters were developed as polynomial regression models. The results showed that verification of using the quadratic regression models derived via Friedman method (Ea=−488.68X2+587.78X+64.104and ln(A)=−106.58X2+116.71X+17.232) had very close agreement with the experiments in entire range of conversion. These regression models could be widely applied in slow pyrolysis and gasification. However, the constants derived via Ozawa–Flynn–Wall​ method (Ea=248.05kJ mol−1and A=3.05x1022 min−1) were simpler for use in some applications which had no effect of pyrolysis at temperature​ below 300 °C or conversion below 50%, like fluidized bed pyrolysis/gasification.